Implementasi HTML 5 dan Image Editor untuk Desain Suvenir pada E-Commerce Souvenir Stuff Berbasis Web dan Mobile - Gladys Nathashya Tansen; Bagus Mulyawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
The development of souvenirs very rapidly, making the gift shop overwhelmed in serving their buyers. This paper presents a new innovation from the world of souvenirs that is making e-commerce applications “Souvenir Stuff” that sell a variety of souvenirs. “Souvenir Stuff” application will complement the features of the existing online souvenir application that is the feature editing or direct design on the application “Souvenir Stuff” and make a new souvenir request. That will reduce the inconsistency that has been happening and facilitate online shopping souvenir transaction. Editing and request features in “Souvenir Stuff” utilize HTML Image Editor that is HTML 5 with fabric.js and canvas library. From the results of tests conducted found that with the souvenir shopping website online and support the design feature is very helpful to the process of buying and selling souvenirs